Population structure and reproductive biology of Uca rapax (Decapoda: Ocypodidae) in a tropical coastal lagoon, southeast Brazil - Costa,Tarso (2009)
A population of the fiddler crab Uca rapax (Smith, 1870) found in Itaipu Lagoon, southeast Brazil, was sampled monthly from July 2006 to June 2007 in order to study population and reproductive features. The sex ratio of the population was statistically different from the expected (1:1) in almost every month, with a predominance of males. The reproductive cycle and the recruitment of juveniles were continuous, with two peaks. The fecundity ranged from 1.110 to 13.189 eggs (4.984 ± 2.493.8), not differing statistically among seasons. In contrast, the relative fecundity (F') and the reproductive intensity index (RII) were highest in the summer. Female size at the onset of sexual maturity was estimated as 6.1 mm and egg diameter ranged from 0.20 to 0.28 mm. The anthropogenic impact on the environment of Itaipu Lagoon probably had adverse effects on the local U. rapax population, as inferred by its low fecundity rates, early maturation age and biased sex ratio.